PENGARUH PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN DAN STRATEGI BISNIS TERHADAP KINERJA PERUSAHAAN PADA PT. SGN MKSO UNIT KEBUN TAKALAR - Nurul Kurnia; Ramly; Muhammad Khaedar Sahib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the influence of the implementation of Environmental Management Accounting and Business Strategy on Company Performance at PT SGN MKSO Takalar Estate Unit. This research uses a quantitative method with an associative approach. Data were collected through the distribution of questionnaires to 40 employees of PT SGN MKSO Takalar Estate Unit and analyzed using SPSS (Statistical Package for the Social Sciences) version 26 through validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results show that the implementation of environmental management accounting and business strategy has a positive and significant effect, both partially and simultaneously, on company performance. This indicates that the greater the company’s responsibility toward the environment, the greater the positive impact on its performance, and that the effective and efficient implementation of business strategies can enhance company performance.